'The floods came and we lost everything': weather extremes and households' asset vulnerability and adaptation in rural Ghana. (3rd April 2018) - Afriyie, Kwadwo; Ganle, John Kuumuori; Santos, Eric
Abstract : Extreme weather events such as flooding have been observed to deplete households' assets and render households vulnerable to shocks and poverty. Few empirical studies have however examined households' asset vulnerability and adaptation to such extreme events in Ghana. Based on qualitative research with two ecologically fragile communities in Ghana, this paper explores the asset vulnerability and adaptation strategies of households against periodic flooding. Findings suggested that households' assets most vulnerable to flooding were farmlands, human health, housing and financial savings. However, flooding did not affect households' assets equally; the effects were gendered and differentiated, often occasioned by inequalities in exposure, vulnerability, access to resources, capabilities and opportunities. Nonetheless, many households are actively adapting their assets by acquiring new knowledge about early warning systems, employing different farming practices and diversifying their assets. Understanding the differences in households' asset vulnerability as well as in the priorities that men and women, as well as the young and old, place on different asset adaptation strategies could therefore be important in the effectiveness of climate change adaptation as well as the sustainability of communities.